Characteristics, Quality, and Safety Issues Identified During Intersocietal Accreditation Commission (IAC) Assessment of Orthopaedic Facilities Utilizing Cone-Beam CT Equipment. Issue 4 (November 2022) - Farrell, Mary B.; Lally, Mary; Davis, Nancy J.
Category: Other Introduction/Purpose: The Intersocietal Accreditation Commission (IAC) began accrediting diagnostic CT facilities in 2007. Recently there has been an increase in the number of outpatient orthopaedic facilities that use cone beam CT (CBCT) equipment seeking accreditation. The accreditation process comprehensively evaluates a facility's daily operation, with quality determined by compliance with the IAC Standards and Guidelines for CT Accreditation. The Standards represent the minimum requirements for staff qualifications, instrumentation, quality assurance, physicist safety surveys, scan procedures, radiation dose optimization, interpretative accuracy, reporting, and quality improvement that a facility must meet to earn accreditation. The Standards are based on the published guidelines of 12 sponsoring professional medical societies, representing various specialties. This investigation aimed to discover characteristics of these facilities and to identify common quality and safety issues. Methods: To become accredited, facilities applying for IAC CT accreditation submit facility demographic data, staff qualifications, policies and procedures, sample quality assurance results, physicist survey reports, radiation dose logs, quality improvement data, and representative case studies via an online application process. The materials are evaluated by trained peer reviewers and findings are reported to the IAC CT Board of Directors for final accreditation decision. The IAC accreditation database was used to extract the characteristics and application findings of all orthopaedic facilities using CBCT that applied for accreditation from 2019-2021. Results: Facility Characteristics Currently, 41 orthopaedic facilities have achieved IAC CT accreditation (see map). The facilities perform a median of 378 scans per site annually (range 75-2400). On average, there were 4 physicians (range 1-20) and 2 technologists (range 0-15) per site. Most sites (n = 32) used CurveBeam CBCT equipment followed by Carestream (n=5) and Planmed (n=4). Facility Deficiencies Identified quality issues included poor scan quality (n=4) such as improper patient positioning or excessive motion artifact and inadequate reporting (n=14) such as inaccurate patient identification information, incomplete exam/technique documentation, or non-compliant report finalization/signature. Identified procedural issues included failure to perform/document routine quality control (n=12) such as phantom testing to ensure the safety of CT scanner operation; missing safety policies such as the medical emergency policy or incomplete clinical scan protocols (n=5); and lack of quality improvement activities (n=5).Finally, facility personnel did not meet staff qualification requirements at 11 sites. Conclusion: In summary, the IAC CT accreditation process rigorously evaluates CT facilities to improve quality and safety. Evaluation of the accreditation findings for outpatient orthopaedic facilities utilizing CBCT equipment and seeking IAC accreditation identified deficiencies at many sites. All facilities were required to rectify the deficiencies prior to being awarded IAC accreditation, and they must continue to monitor quality and safety to remain accredited.